2008
DOI: 10.1071/ar07281
|View full text |Cite
|
Sign up to set email alerts
|

Genotype×environment interaction for wheat yield in different drought stress conditions and agronomic traits suitable for selection

Abstract: Wheat cultivars grown in south-eastern Europe are exposed to variable rainfed environments. Climate change predictions indicate that the frequency of dry years will likely increase in the future. This study examined relationships among agronomic traits and some drought indices with grain yield as influenced by genotype and environment. In a 4-year experiment, 100 cultivars and landraces of bread wheat (Triticum aestivum L.) from different countries were tested under 3 watering regimes: fully irrigated, rainfed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
3
22
1
Order By: Relevance
“…Lots did not significantly affect varying of seed germination and dormancy as it was expected considering that regions of central, eastern and south-eastern Serbia are geographically small, do not differ much in climatic and edaphic conditions, and the applied growing practices were also similar. Although several previous studies of various species showed that differences among consecutive years were larger than differences among test sites within a region of south-east Europe (Rizza et al, 2004;Sudarić et al, 2006;Dodig et al, 2008), the year in the present study did not have a significant effect on the variation of seed germination and dormancy of the three observed species of fodder crops.…”
Section: Discussioncontrasting
confidence: 40%
“…Lots did not significantly affect varying of seed germination and dormancy as it was expected considering that regions of central, eastern and south-eastern Serbia are geographically small, do not differ much in climatic and edaphic conditions, and the applied growing practices were also similar. Although several previous studies of various species showed that differences among consecutive years were larger than differences among test sites within a region of south-east Europe (Rizza et al, 2004;Sudarić et al, 2006;Dodig et al, 2008), the year in the present study did not have a significant effect on the variation of seed germination and dormancy of the three observed species of fodder crops.…”
Section: Discussioncontrasting
confidence: 40%
“…The genotype vs. moisture regime interaction for WU was highly significant (Table 2) indicating water use pattern of genotypes changed with water availability. This is in conformity with result of Dodig et al, (2008). BL2800, Gautam, Hartog, and Dharwar dry had higher WU values in non stressed environment in contrast to SeriM82, NPGR6696, Vijaya and Bhrikuti which used minimum water during the test period.…”
Section: Phenological Parameterssupporting
confidence: 70%
“…Biomass per plant is a very important selection criterion for developing genotypes with high yield and terminal water stress tolerance (Dodig et al, 2008). Ehdaie et al (2006 a) reported that high internode specific weight and balanced partitioning of stem length into lower and upper internodes are important in genotypic accumulation and mobilisation of stem Water-soluble carbohydrates accumulation in peduncle of wheat and its relationship to morpho-anatomical and productive traits reserves in wheat.…”
Section: Discussionmentioning
confidence: 99%